Characterization of the observe zone of the ESC 2015 high-sensitivity cardiac troponin 0 h/1 h-algorithm for the early diagnosis of acute myocardial infarction. (15th March 2016) - Nestelberger, Thomas; Wildi, Karin; Boeddinghaus, Jasper; Twerenbold, Raphael; Reichlin, Tobias; Giménez, Maria Rubini; Puelacher, Christian; Jaeger, Cedric; Grimm, Karin; Sabti, Zaid; Hillinger, Petra; Kozhuharov, Nikola; et al.
Abstract: Objective: The novel high-sensitivity cardiac troponin (hs-cTn) 0 h/1 h-algorithm substantially improves the early triage of patient's assigned "rule-out" or "rule-in" of acute myocardial infarction (AMI), while diagnostic uncertainty remains in that 25–30% of patients assigned to "observe". We aimed to better characterize these patients. Methods: In a prospective multicenter diagnostic study, we applied the hs-cTnT 0 h/1 h-algorithm in 2213 unselected patients presenting with symptoms suggestive of AMI to the emergency department. The final diagnosis was adjudicated by two independent cardiologists using all available information. Survival at 720-days was the prognostic endpoint. Findings were validated using a hs-cTnI 0 h/1 h-algorithm. Results: Twenty-four percent (n = 523) of patients were assigned to "observe" by the hs-cTnT 0 h/1 h-algorithm. These patients differed significantly in multiple characteristics from "rule-out" and "rule-in" patients: they were older, in 75% male, and very often (57%) had pre-existing coronary artery disease (CAD). Diagnostic uncertainty for the presence of an AMI/UA was high. Only 39% of patients were suitable for coronary computed tomography angiography (CCTA). The most common final adjudicated diagnoses were non-cardiac disease (38%), non-coronary cardiac disease (24%), unstable angina (UA, 21%), and AMI (15%). Absolute hs-cTnT-changes within 3 h had the highest diagnostic accuracy for AMI (AUC 0.86). Cumulative 720-day survival rate was 86%, which was significantly lower as compared to "rule-out" (p < 0.001) and comparable to "rule-in" (p = ns). Findings were similar for the hs-cTnI "observe" zone. Conclusion: "Observe" patients are typically elderly men with pre-existing CAD and high long-term mortality. Absolute hs-cTn-changes within 3 h, functional stress imaging and coronary angiography are the key diagnostic modalities.